MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA (SMP) INKLUSI TAMAN PENDIDIKAN DAN ASUHAN JEMEBR - Sholihah, Imro'atus; Ahmansuro, Luluk (IHTIROM : Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to eliminate discrimination between children with special needs who can study together with normal children, so that it affects the growth and development of students.The focus of this research is "Learning Management of Islamic Religious Education in SMP Inclusion TPA Jember". Furthermore, it is described in several research questions as follows: 1) How is the planning of Islamic Religious Education learning at the Jember TPA Inclusion Middle School? 2) How is the Implementation of Islamic Religious Education Learning at the Jember TPA Inclusion Middle School? 3) How is the evaluation of Islamic Religious Education learning in SMP Inclusion TPA Jember?This study uses qualitative research. The approach used is a descriptive qualitative approach. Data collection techniques are observation, interviews, and documentation. While the technical analysis of data using Triangulation of Sources and Techniques. The result of this research is that there is a difference between planning, implementation, and evaluation. The absolute difference lies in planning, namely the procurement of individual learning plans (PPI) for children with special needs when in regular classes and not in normal children. Second, in the implementation of learning, there is special assistance for children with special needs in regular classes, while for normal children there is only 1 teacher. Third, in terms of evaluation, there are two kinds of assessment sources, namely from Islamic Religious Education teachers and teachers with special needs. In addition, it is seen from the KKM standard (Minimum Completeness Criteria). The KKM standard (Minimum Completeness Criteria) for children with special needs is 65 while the regular one is 75.